Dynamic effects of communication delay, failure rates, and speed on UAV swarm formation - Lucchesi, Laércio; Endler, Markus; Souza, Bruno José Olivieri de (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2024)
This study, focusing on Unmanned Aerial Vehicles (UAVs) in a leader/follower network architecture, addresses the increasing reliance on UAVs operating in groups or swarms for applications like reconnaissance and target surveillance. This study tackles the problem on how the swarm dynamics and its coordination, i.e. the drone’s movement synchronization, is impacted by varying operational conditions such as leader speed, communication delay and failures. Utilizing an advanced Python-based simulation framework, the research evaluates the impact of different parameters on swarm dynamics in various UAV formation scenarios, specifically in relation to networking and communication issues. The study’s principal contribution lies in its systematic investigation of how these parameters influence key performance metrics like Leadership Error and Formation Error. Experimental results reveal critical insights into UAV swarm behavior, demonstrating that while high speeds and communication failures impact formation integrity and leader-following accuracy, the systems show resilience to extended communication delays.